2021
DOI: 10.3390/nano11051284
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Physical and Mechanical Properties of Carbon Nanotubes—Graphene-Based Sandwich Composite Pressure Sensor

Abstract: In this work, piezoresistive properties of graphene-multiwalled carbon nanotubes (MWCNTs) composites are investigated, characterized, and compared. Sandwich-type composite piezoresistive pressure-sensitive sensors (Ag/Graphene-MWCNT/Ag) with the same diameters, but different fabrication pressures and thicknesses were fabricated using the mortar and pestle/hydraulic press technique. To produce low-electrical-resistance contacts, both sides of the composite sensors were painted with silver (Ag) paste. All the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The approach chosen in the research opens up wide possibilities for controlling the composites' structure and properties by choosing the initial waste powders introduced into the starting powder mixture to form the strong metal matrix and adding the solid lubricant by the necessary amount [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The approach chosen in the research opens up wide possibilities for controlling the composites' structure and properties by choosing the initial waste powders introduced into the starting powder mixture to form the strong metal matrix and adding the solid lubricant by the necessary amount [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, artificial intelligence has gradually been becoming a quite hot research area and is regarded as the core technology leading the fourth industrial revolution, which means that human labor can be replaced in principle by intelligent robots. Flexible strain sensors can be integrated into machines as a sensing element for machine perception, and human-robot interaction [53,[210][211][212][213][214][215][216][217][218][219][220], which is crucial for Industry 4.0. Recently, Zhao et al [54] reported a flexible thin-film e-skin composed of CNTs/PDMS composite film with layered structure and interdigital electrode.…”
Section: Human-machine Interactionmentioning
confidence: 99%
“…Wood and crop leftovers are also used as a biofuel [8,9]. Alternative energy sources that are nearby available, particularly renewable, and ecologically beneficial by helping CO 2 balance should be investigated and used to meet energy demands [10,11]. Forestry, agricultural leftovers, and residues are being investigated as a critical resource of bioenergy and biomaterials.…”
Section: Introductionmentioning
confidence: 99%